Melanoma acral: a propósito de un caso - Valenzuela A. , Fernando; Yagnam D., Mathías; Zemelman D., Viviana; Morales H. , Claudia; Valenzuela Y. , Carlos Y. (Revista Hospital Clínico Universidad de Chile, 2013)
Acral melanoma is an uncommon cutaneous malignant tumour, which may arise on the foot. A 73 years old female patient presented with an ulcerated lesion on the sole of the left foot for one year, associated to an older pigmented lesion. The biopsy of both lesions, showed “in situ cutaneous melanoma” in the pigmented lesion and “infiltrating cutaneous melanoma” in the ulcerated lesion. In this case report is discussed the epidemiology of acral melanoma around the world, showing the importance in early recognition and proper management.